1997
DOI: 10.1139/z97-126
|View full text |Cite
|
Sign up to set email alerts
|

Are staged dyadic encounters useful for studying aggressive behaviour of arvicoline rodents?

Abstract: We investigated the aggressiveness of adult prairie voles (Microtus ochrogaster) in dyadic encounters staged in different types of arena trials to determine if responses differed (i) between neutral arena trials conducted in the laboratory and resident-intruder trials conducted in the field, (ii) between trials staged before and after 3 months of isolation from social contact, (iii) between voles reared in the laboratory and voles reared in the field, and (iv) among trials staged with the same individual over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…The levels of behavior exhibited in the intrasexual aggression test were similar to those previously published (Getz, 1962; Harper and Batzli, 1997; Stribley and Carter, 1999; Bales and Carter, 2003a). Aggressive behavior (lunging and chasing) was low and did not differ between males and females.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The levels of behavior exhibited in the intrasexual aggression test were similar to those previously published (Getz, 1962; Harper and Batzli, 1997; Stribley and Carter, 1999; Bales and Carter, 2003a). Aggressive behavior (lunging and chasing) was low and did not differ between males and females.…”
Section: Resultssupporting
confidence: 86%
“…Subjects were given a dyadic encounter test for intrasexual aggression (Winslow et al, 1993; Harper and Batzli, 1997; Bowler et al, 2002; Bales and Carter, 2003a). The test subject was placed in a novel cage with an unfamiliar stimulus animal of the same sex and approximate age and size.…”
Section: Methodsmentioning
confidence: 99%
“…These may not indicate aggression levels toward a same-sex conspecific. One study that examined aggression in same-sex dyads observed more aggressive behaviors in males than females, although the effect of sex was not statistically tested (Harper & Batzli, 1997). Our experiments observed strong and weak dominance in both male and female vole pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Staged dyadic encounters are an approved tool to approach to the aggressive behaviour of voles and lemmings (Harper and Batzli 1997). We targeted focal animals by setting the most commonly used traps for these individual animals early in the morning and then checking the traps after 2–4 h. Upon capture, an opponent was presented to the focal female at the point of capture in a clean arena ( macrolon standard cage 42 × 28 cm with an extension of wall height to 30 cm) for 10 min.…”
Section: Methodsmentioning
confidence: 99%